ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI BAWANG MERAH DI DESA FAFOE KECAMATAN MALAKA BARAT KABUPATEN MALAKA - Yovita Luruk Lekik; Tomycho Olviana; Paulus Un (Undana Press, 2022)
The aims of this study was to find out; 1) the characteristics of farmers in Fafoe Village, West Malaka Subdistrict, Malaka Regency. 2) To determine the factors those affect the production of shallots in West Malacca District, Malaka Regency. This research used quantitative methods. The results of this study indicate that; 1) Characteristics of shallot farmers in Fafoe Village, West Malaka Subdistrict, Malaka Regency, which seen from two aspects, namely aspects based on age and education. There were 27 farmers aged 15-55 years (71.5%) who are still productive and 11 farmers aged 15-55 years (28.94%), thus from 11 farmers it can be said that they were not productive again. Meanwhile, 32 farmers were elementary education with a percentage of 84.21%, 4 farmers were junior high school education with a percentage of 10.52%, followed by 2 respondents were high school education with a percentage of 5.26%. 2) The factors which affecting the production of shallots in Fafoe Village, West Malaka Subdistrict, Malaka Regency, based on the results of the study showed that the land area, number and seeds had a significant effect on the amount of shallot production. Meanwhile, labor, fertilizers and pesticides did not significantly influence to the amount of shallot production. The impact of production factors on the amount of shallot production was 98.8%.